J. Bellamy, Crime and Public Order in England in the later Middle Ages - Salmonowicz, Stanisław (Czasopismo Prawno-Historyczne, 1974)
Recenzja: John Bellamy, Crime and Public Order in England in the Later Middle Ages, London—Toronto 1973, ss. 229.